Breastfeeding in Mothers with Multiple Sclerosis: The German Experience - Aigner, Stefanie; Huhn, Konstantin; Cepek, Lukas; Hellwig, Kerstin; Nickel, Florian; Bayas, Antonios (Breastfeeding Medicine, 2023)
Background: Many female people with multiple sclerosis (pwMS) are in childbearing age; however, only few data exist about the situation of breastfeeding in pwMS.Objective: Our study analyzed breastfeeding rate and duration, reasons for weaning, and the impact of disease severity on successful breastfeeding in pwMS.Methods: The study included pwMS giving birth within 3 years before study participation. Data were collected by structured questionnaire.Results: Compared to published data, we found a significant difference (p = 0.0007) between the nursing rate in the general population (96.6%) and females with MS (85.9%). However, a higher rate of exclusive breastfeeding could be observed in our study population for 5-6 months in 40.6% of pwMS versus 9% for 6 months in the general population. In contrast, total breastfeeding duration in our study population was shorter (18.8% for 11-12 months) than in the general population (41.1% for 12 months). Reasons for weaning were predominantly (68.7%) related to breastfeeding barriers based on MS. No significant impact of prepartum or postpartum education on the breastfeeding rate could be observed. Prepartum relapse rate and prepartum disease-modifying drugs had no effect on breastfeeding success.Conclusion: Our survey provides an insight into the situation of breastfeeding in pwMS in Germany.
CRIS-Team WoS Importer:2023-03-17

Correction to: Expression of Inflammatory Mediators in Biofilm Samples and Clinical Association in Multiple Sclerosis Patients in Remission—A Pilot Study (Life, (2024), 14, 3, (367), 10.3390/life14030367) - Fehlhofer, Jakob Paul; Ries, Jutta; Nickel, Florian; Rothhammer, Veit; Schwab, Stefan; Kesting, Marco Rainer; Buchbender, Mayte (Life, 2024)
The reference 22 was deleted in the original publication [1]. With this correction, the order of some references has been adjusted accordingly. The authors state that the scientific conclusions are unaffected. This correction was approved by the Academic Editor. The original publication has also been updated.
CRIS-Team Scopus Importer:2024-09-06

Eculizumab use in neuromyelitis optica spectrum disorders: real-world evidence from Germany and Austria - Ringelstein, M.; Asseyer, S.; Lindenblatt, G.; Fischer, K.; Pul, R.; Ozalp, S. -H.; Lohmann, L.; Giglhuber, K.; Haeussler, V.; Karenfort, M.; Hellwig, K.; Paul, F.; et al. (MULTIPLE SCLEROSIS JOURNAL, 2022)
CRIS-Team WoS Importer:2022-12-09

Eculizumab Use in Neuromyelitis Optica Spectrum Disorders Routine Clinical Care Data From a European Cohort - Ringelstein, Marius; Asseyer, Susanna; Lindenblatt, Gero; Fischer, Katinka; Pul, Refik; Skuljec, Jelena; Revie, Lisa; Giglhuber, Katrin; Häußler, Vivien; Karenfort, Michael; Hellwig, Kerstin; Paul, Friedemann; et al. (Neurology, 2024)
Background and Objectives Attack prevention is crucial in managing neuromyelitis optica spectrum disorders (NMOSDs). Eculizumab (ECU), an inhibitor of the terminal complement cascade, was highly effective in preventing attacks in a phase III trial of aquaporin-4 (AQP4)-IgG seropositive(+) NMOSDs. In this article, we evaluated effectiveness and safety of ECU in routine clinical care. Methods We retrospectively evaluated patients with AQP4-IgG+ NMOSD treated with ECU between December 2014 and April 2022 at 20 German and 1 Austrian university center(s) of the Neuromyelitis Optica Study Group (NEMOS) by chart review. Primary outcomes were effectiveness (assessed using annualized attack rate [AAR], MRI activity, and disability changes [Expanded Disability Status Scale EDSS]) and safety (including adverse events, mortality, and attacks after meningococcal vaccinations), analyzed by descriptive statistics. Results Fifty-two patients (87% female, age 55.0 ± 16.3 years) received ECU for 16.2 (interquartile range [IQR] 9.6 – 21.7) months. Forty-five patients (87%) received meningococcal vaccination before starting ECU, 9 with concomitant oral prednisone and 36 without. Seven of the latter (19%) experienced attacks shortly after vaccination (median: 9 days, IQR 6–10 days). No postvaccinal attack occurred in the 9 patients vaccinated while on oral prednisone before starting ECU and in 25 (re-)vaccinated while on ECU. During ECU therapy, 88% of patients were attack-free. The median AAR decreased from 1.0 (range 0–4) in the 2 years preceding ECU to 0 (range 0–0.8; p < 0.001). The EDSS score from start to the last follow-up was stable (median 6.0), and the proportion of patients with new T2-enhancing or gadolinium-enhancing MRI lesions in the brain and spinal cord decreased. Seven patients (13%) experienced serious infections. Five patients (10%; median age 53.7 years) died on ECU treatment (1 from myocardial infarction, 1 from ileus with secondary sepsis, and 3 from systemic infection, including 1 meningococcal sepsis), 4 were older than 60 years and severely disabled at ECU treatment start (EDSS score ≥ 7). The overall discontinuation rate was 19%. Discussion Eculizumab proved to be effective in preventing NMOSD attacks. An increased risk of attacks after meningococcal vaccination before ECU start and potentially fatal systemic infections during ECU—particularly in patients with comorbidities—must be considered. Further research is necessary to explore optimal timing for meningococcal vaccinations. Classification of Evidence This study provides Class IV evidence that eculizumab reduces annualized attack rates and new MRI lesions in AQP4-IgG+ patients with NMOSD.
CRIS-Team Scopus Importer:2024-10-25

Expression of Inflammatory Mediators in Biofilm Samples and Clinical Association in Multiple Sclerosis Patients in Remission—A Pilot Study - Fehlhofer, Jakob Paul; Ries, Jutta; Nickel, Florian; Rothhammer, Veit; Schwab, Stefan; Kesting, Marco Rainer; Buchbender, Mayte (Life, 2024)
Multiple sclerosis (MS) is a chronic inflammatory autoimmune disease of unknown etiology that affects the central nervous system and can lead to neurological impairment. Our aim was to determine whether MS patients also show inflammatory changes in the oral cavity more frequently than healthy individuals. For this purpose, we examined plaque samples for various mediators and their correlation with clinical findings. A study group (MS) and a control group were examined and compared. The plaque samples were analyzed for the expression of interleukins (IL-2, -6, -10), matrix metalloproteinases (MMP-7, MMP-9), and a surface antigen CD90 by quantitative real-time PCR. The clinical parameters examined were the Mombelli plaque index; bleeding on probing (BOP) index; periodontal pocket depth; and decayed, missing, and filled tooth (DMFT) index. The expression of MMP9 was significantly (p = 0.035) higher in the control group. The expression of IL-2 was increased four-fold in the MS group; however, this difference was not statistically significant. The mean PD (p < 0.001) and BOP index (p = 0.029) values were increased in the study group. The clinical parameters of the BOP index and PD were significantly amplified in the MS patients. However, no causal relationship between the investigated inflammatory mediators and the clinical findings could be established in this case series.
CRIS-Team Scopus Importer:2024-05-24
Keywords: cytokine expression; multiple sclerosis; oral hygiene; periodontitis

Immune signatures of checkpoint inhibitor-induced autoimmunity-A focus on neurotoxicity. - Müller-Jensen, Leonie; Schulz, Axel R.; Mei, Henrik E.; Mohr, Raphael; Ulrich, Claas; Knape, Philipp; Frost, Nikolaj; Frischbutter, Stefan; Kunkel, Desiree; Schinke, Christian; Ginesta Roque, Lorena; Maierhof, Smilla K.; et al. (Neuro-Oncology, 2024)
BACKGROUND: Neurologic immune-related adverse events (irAE-n) are rare but severe toxicities of immune checkpoint inhibitor (ICI) treatment. To overcome diagnostic and therapeutic challenges, a better mechanistic understanding of irAE-n is paramount. METHODS: In this observational cohort study, we collected serum and peripheral blood samples from 34 consecutive cancer patients with irAE-n (during acute illness) and 49 cancer control patients without irAE-n (pre- and on-ICI treatment, n = 44 without high-grade irAEs, n = 5 with high-grade nonneurologic irAEs). Patients received either anti-programmed cell death protein (PD)-1 or anti-PD ligand-1 monotherapy or anti-PD-1/anti-cytotoxic T-lymphocyte-associated protein-4 combination therapy. Most common cancers were melanoma, lung cancer, and hepatocellular carcinoma. Peripheral blood immune profiling was performed using 48-marker single-cell mass cytometry and a multiplex cytokine assay. RESULTS: During acute illness, patients with irAE-n presented higher frequencies of cluster of differentiation (CD)8+ effector memory type (EM-)1 and central memory (CM) T cells compared to controls without irAEs. Multiorgan immunotoxicities (neurologic + nonneurologic) were associated with higher CD8+ EM1 T cell counts. While there were no B cell changes in the overall cohort, we detected a marked decrease of IgD- CD11c+ CD21low and IgD- CD24+ CD21high B cells in a subgroup of patients with autoantibody-positive irAE-n. We further identified signatures indicative of enhanced chemotaxis and inflammation in irAE-n patients and discovered C-X-C motif chemokine ligand (CXCL)10 as a promising marker to diagnose high-grade immunotoxicities such as irAE-n. CONCLUSIONS: We demonstrate profound and partly subgroup-specific immune cell dysregulation in irAE-n patients, which may guide future biomarker development and targeted treatment approaches.
EVALuna2:541088

Meningitis and intracranial abscess due to Mycoplasma pneumoniae in a B cell-depleted patient with multiple sclerosis - Madžar, Dominik; Nickel, Florian; Rothhammer, Veit; Gölitz, Philipp; Geißdörfer, Walter; Dumke, Roger; Lang, Roland (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Mycoplasma pneumoniae, a frequent respiratory pathogen, can cause neurological disease manifestations. We here present a case of M. pneumoniae as cause of meningitis and occurrence of an intracranial abscess as a complication of mastoiditis with septic cerebral venous sinus thrombosis in a patient with multiple sclerosis on anti-CD20 therapy.
CRIS-Team Scopus Importer:2024-09-20
Keywords: Abscess; Anti-CD20 antibody; Complication; Mastoiditis; Multiple sclerosis; Mycoplasma pneumoniae; Ocrelizumab; Rituximab; Septic cerebral venous sinus thrombosis

Situation of breastfeeding in multiple sclerosis - a questionnaire survey in Germany - Aigner, S.; Huhn, Konstantin; Cepek, L.; Hellwig, K.; Nickel, Florian; Bayas, A. (MULTIPLE SCLEROSIS JOURNAL, 2022)
CRIS-Team WoS Importer:2022-12-09